One Belt One Road Initiative and Latin America: About the TVS project and other future alternatives - Carrasco, Pablo (Latin American Journal of Trade Policy, 2021)
The Chinese initiative “One Belt One Road” which aims to connect Asia with Europe and Africa by land and sea, emulating the old Silk Road, also aims to expand to Latin America through international cooperation and investments in railway infrastructure. Although in Chile the railroad project between Santiago and Valparaíso (TVS project) was canceled due to its high cost, this article will address two questions in this context: 1) What factors explain the presence of China in Latin America?; and, 2) Despite the closure of the TVS train project, are there alternatives to consolidate China’s international cooperation and investments in Latin America? What are their advantages and disadvantages?